Clinico-Cytological Spectrum of Lesions in Lymph Nodes of Patients at a Tertiary Care Centre - Dr. Akansha Anu; Dr. Vaishali D Kotasthane; Dr Dhananjay S Kotasthane (International Journal of Pharma and Bio Sciences, 2023)
Enlarged lymph node is one of the most frequent clinical manifestations of patients visiting the outpatient department subjected to FNAC. It is the first line of investigation in evaluating lymphadenopathy due to the frequent involvement of lymph nodes in regional and systemic disease & due to easy accessibility. Thus, it is often used as a safe substitute for excision biopsy. The present study aimed to study the clinical and cytomorphological features of enlarged Lymph nodes by Fine Needle Aspiration Cytology in patients with Lymphadenopathy. The objective of the study was to describe the cytomorphological features of enlarged Lymph nodes involved in various etiologies, to categorize clinical features in patients with lymphadenopathy, to assess the frequency of lymphadenopathy in different age groups and gender, and to categorize varied etiologies of Lymph node enlargement according to site. It was an observational study. A total of 155 cases with enlarged lymph nodes were studied during the study period from December 2020 to November 2022. The present study found that out of 155 cases, 149 cases (96.12%) were adequate for cytological diagnosis. The study showed slight male preponderance with M: F ratio of 1.06:1, mean age was 45 years. Fever was the most common clinical presentation besides lymphadenopathy, with 53.33% of cases. The cervical group of lymph nodes was the most common group of lymph nodes affected at 41.29%. Of 149 cases, non-neoplastic lesions accounted for 92.61%, and neoplastic lesions for 7.38%. Among the non-neoplastic lesions, caseating tubercular lymphadenitis was the most common finding accounting for 39.85% of cases, followed by reactive lymphadenitis in 35.50%, granulomatous lymphadenitis in 13.04% of cases, suppurative lymphadenitis in 7.24% & cold abscess in 2.89% cases. Infectious mononucleosis and Parasitic infestation were found in one case each. Among the neoplastic lesions, metastasis in the lymph nodes was more common than primary lymphomas; the most commonly involved lymph node was the cervical lymph node. Metastasis from squamous cell carcinoma was seen in 36.36% of cases, metastasis from adenocarcinoma was seen in 9.09% of cases, and from other sites was seen in 36.36% of cases. The present study concluded that tuberculous lymphadenitis is still rampant, the most common cause of lymphadenopathy. FNAC is an excellent diagnostic procedure that can establish a rapid cytological diagnosis in non-neoplastic and neoplastic lesions of lymph nodes and helps in patient care management.